Comparison Of Teacher Recruitment And Development In Indonesia And England - Zahratul Azizah; Sri Mariya; Nurhizrah Gistituati; Rusdinal; Azwar Ananda (CV. AFDIFAL MAJU BERKAH, 2022)
The teacher is a profession that has an important role in realizing quality education, especially in the learning process in formal schools. For this reason, there needs to be a selection carried out in selecting prospective teachers and also a coaching process so that the teaching profession contributes to success in the world of education. This study provides an overview of the differences of teacher recruitment and development in Indonesia and England. The method used in this study is a literature study obtained from various writings in journals and books. The results obtained in this study indicate several comparison: 1) there are two types of teacher recrutment in Indonesia, namely selection of civil servant teachers in public schools conducted by the government under the auspices of the Ministry of Education and Culture, and selection carried out by foundations to become honorary teachers or part-time teachers at private schools with the provisions and rules made by the school itself. While in England, the selection is carried out by each school that will accept prospective teachers with the terms and conditions that have been determined and apply to public schools and private schools; 2) Development of teachers in Indonesia is carried out after qualifying to become teachers (both civil servants and non-civil servants) which is provided by the government or private sector, while in England, coaching is carried out before and after becoming a teacher which is the responsibility of each school.